2000
DOI: 10.1002/(sici)1521-3773(20000218)39:4<692::aid-anie692>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

New Results of Chemical Transport as a Method for the Preparation and Thermochemical Investigation of Solids

Abstract: Chemical transport experiments are a valuable aid of great potential in the synthesis and thermochemical characterization of solids. Compounds of interest can often only be crystallized by this method. The use of a transport balance allows very detailed observations, particularly of the course of the experiment over time (simultaneous or sequential deposition of multiple-phase solids). The computer program CVTRANS enables a quantitative thermochemical description of the experiment based on the cooperative tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 138 publications
2
33
0
1
Order By: Relevance
“…Solid state reactions of the elements tend to be time consuming (days to weeks) and are heavily dependent on diffusion distances in the solid state; thus, multiple heating and grinding cycles must be employed [8,9]. The use of molten media or exploitation of vapor transport processes using multizoned furnaces can decrease the heating time and result in well-formed crystals [10]. Solidstate metathesis [11,12] and solvothermal synthesis [13][14][15] are faster methods for generating transition-metal phosphides and can be tuned to prepare materials that are microcrystalline or nanocrystalline.…”
Section: Introductionmentioning
confidence: 99%
“…Solid state reactions of the elements tend to be time consuming (days to weeks) and are heavily dependent on diffusion distances in the solid state; thus, multiple heating and grinding cycles must be employed [8,9]. The use of molten media or exploitation of vapor transport processes using multizoned furnaces can decrease the heating time and result in well-formed crystals [10]. Solidstate metathesis [11,12] and solvothermal synthesis [13][14][15] are faster methods for generating transition-metal phosphides and can be tuned to prepare materials that are microcrystalline or nanocrystalline.…”
Section: Introductionmentioning
confidence: 99%
“…A temperature gradient is typically established between the source zone and the growth zone in a sealed ampule using values from thermodynamic calculations. As a result, bulk crystals are slowly grown in the zone where formation is favored …”
mentioning
confidence: 99%
“…As a result, bulk crystals are slowly grown in the zone where formation is favored. [37][38][39][40] Although CVT is ubiquitously used to synthesize bulk crystals, it was only recently reported that atomically thin TMDs, including WS 2 , can be grown using CVT in a sealed ampule by carefully controlling mass transport. [41,42] While using I 2 and metal chlorides as transport agents, the presented closed-tube technique still requires metal oxides and sulfur as precursors, akin to CVD where stoichiometry is always a consideration.…”
mentioning
confidence: 99%
“…Phase analysis of the resulting intense yellow powder revealed (Hg 2 ) 2 As 2 O 7 as the main phase and (Hg 3 ) 3 (AsO 4 ) 4 [4] and HgAs 2 O 6 [5,6] as by-products. Plate-like canary yellow single crystals of the title-compound with an edge-length of up to 0.8 mm were grown by subsequent chemical transport reactions [8] of the polycrystalline material [50 mg of HgCl 2 (Merck, p.A.) as transport agent, temperature gradient 550 Ǟ 500°C, reaction time 5 d].…”
Section: Methodsmentioning
confidence: 99%